2011
DOI: 10.1371/journal.pone.0024232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Coronary Tortuosity in Patients with Coronary Artery Disease

Abstract: BackgroundCoronary tortuosity (CT) is a common coronary angiography finding. The exact pathogenesis, clinical implication and long-term prognosis of CT are not fully understood. The purpose of this study is to investigate the clinical characteristics of CT in patients with suspected coronary artery disease(CAD) in a Chinese population.MethodsA total of 1010 consecutive patients underwent coronary angiography with complaints of chest pain or related symptoms were included in the present study (544 male, mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
81
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 18 publications
12
81
1
3
Order By: Relevance
“…Women were found to have more CT and smaller heart dimensions in comparison with men, and this was thought to be responsible for this trend [4,15]. A higher proportion of elderly people affected with CT has also been documented [3].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Women were found to have more CT and smaller heart dimensions in comparison with men, and this was thought to be responsible for this trend [4,15]. A higher proportion of elderly people affected with CT has also been documented [3].…”
Section: Discussionmentioning
confidence: 95%
“…Li et al [15], found that CT was positively correlated with essential hypertension. Tortuosity of coronary arteries is also a common finding seen with hypertension due to elongation and dilatation of the arteries associated with left ventricular hypertrophy [4,15]. The authors assumed that arteries may become tortuous due to reduced axial strain and hypertensive pressure in an elastic cylindrical arterial model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronary tortuosity (CT) is a finding commonly found at the angiographic evaluation 1 . This condition is defined by the presence of ≥3 bends (≥45° change in vessel direction) along the main trunk of at least one coronary artery, present both in systole and in diastole 2 .…”
mentioning
confidence: 99%